Pengembangan Video Pembelajaran Interakti Menggunakan Aplikasi Powtoon IPAS Materi Perubahan Wujud Benda - Subhan, Muhammad; Amril, Amril; Rusita Dewi, Sintya Trisna (Institut Agama Islam Daruttaqwa Gresik, 2023)
The background of this research is that students find it difficult to understand the science learning material provided by the teacher, they seem less enthusiastic about learning and there are still many students who are engrossed in chatting with their friends during the learning process. During the learning process itself, it is still centered on the teacher, this causes students to be less interested in participating in the process of learning activities which they consider boring. This study aims to produce learning media that have valid, practical, and effective criteria. This research is development research. The model used for this development is the ADDIE development model. This research was conducted at SDN 095/VIII in Karang Dadi Village, Tebo Regency in grade IV of Elementary School. The results of the interactive learning video assessment using the Powtoon application were carried out by expert validators to get a result of 89.22% in a very valid category. The results of the practicality value carried out by the teacher obtained a score of 98.7% in the very practical category and the practicality value by students obtained 96.4% in the very practical category so the average practicality result by the teacher and students was 97.5% in the very category. practical. The effectiveness results were obtained from the learning outcomes of students who scored above the KKTP with a result of 84.8 in the very effective category.